The validity and the reliability of Turkish version of children's sleep habits questionnaire [Çocuk uyku alişkanliklari anketinin türkçe geçerliliǧi ve güvenilirliǧi] - (:unkn) unknown (My University, 2010)
Objective: The objective of this study was to examine the validity and the reliability of Turkish version of Children's Sleep Habits Questionnaire (CSHQ)-Abbreviated Form. Methods: The sample consisted of 1749 1st, 2nd, 3rd, and 4th grade elementary schoolchildren. The parents were asked to complete the CSHQ, sociodemographic form, and a question list assessing the behavioral and emotional problems of children. Internal consistency, test-retest reliability, and construct validity of the CSHQ were investigated. Results: Cronbach's alpha coefficient was determined as 0.78. The test retest correlation coefficient was 0.81 (p<0.001). As a result of factor analysis 11 factors were determined. Additional analysis regarding the construct validity indicated that the total sleep scores did not differ by age and gender (p>0.05), yet the scores tended to increase with decreasing socio-economic status (p<0.001). There were statistically significant relationships between all behavioral and emotional parameters and the presence of sleep problems. Conclusion: These results suggest that Children's Sleep Habits Questionnaire, which is a parent proxy-report, is a valid and reliable instrument for assessing sleep habits and screening possible sleep problems of Turkish children.
Keywords: Child; Questionnaire; Reliability; Sleep problems; Validity